Práticas e reflexões sobre educação alimentar: uma narrativa interdisciplinar - Tomazoni, Ana Maria Ruiz (2014)
Food is bonded to the human beings through its physiologic, emotional, social, historic, cultural and psychological functions, what emphasizes its educative potential. The purpose of this dissertation is to present experiences involving food direct and indirectly. This dissertation is the result of special classes given by the author along thirty years of experience that have been developed at her culinary school and in other external courses. With the results are discussed and presented several projects involving experts of different areas of specialization, researches, books and dissertations published which are related to the experience with food, meeting the current legislations related to the human beings, the citizens rights, to education, to food, to healthy and to life quality. The interdisciplinary theme, researched and proposed by Ivani Fazenda, is introduced along the dissertation and it was presented in the narrative format, what allowed the author to discuss several movements that can maybe turn food into an instrument of education reflected in educational practices. Some strategies were presented in order to arrange the analyses and to awake the senses, among them, the projects of practical experiences: children and adolescents, learning how to eat and cooking with nutrition, which allow a broad interaction with several sorts of food, materials, interactive videos and ceremonial. The results consolidated the validation of the narrative and of the interdisciplinary attitudes as a track to the shared and construed learning, also demonstrating that food has skills to be a suitable tool in the education process, taking advantage of its social, cultural, emotional and physiologic appeals. It is expected that this research encourages the development of new projects in this area and stimulates food practices and learnings that may generate new dissertations in this educative path. Ultimately, the research expects to involve people beyond the school walls to create a curriculum dedicated to the food identity and heritage